ANALISIS KESALAHAN SISWA SMK LLPM PADALARANG DALAM MENYELESAIKAN SOAL BENTUK AKAR - Febriani Dwi Maharani; Anik Yuliani (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Mathematics became one of the mare lessons that a man learned, based on logic and which ranged from the easiest to the most complicated. In addition, we also provide a wide range of products that you can choose according to your needs. analyzing students' mistakes in solving problems can find out whether a student has mastered a material or not. This study has the purpose to describe and analyze the errors of students in solving the soul number root form and the factors causing the error. This type of research uses a description of the quality of the research subject is a student of Class X SMC LPM Padalarang. The sample to obtain data were 6 students representing high, medium and low ability students who were classified from the average results of the root form question test. The Data will be generated in the form of the results of the test questions in the form of descriptions and interviews with several students. From the data collection will result in the analysis of students ' difficulties in solving the problem of root form numbers and the factors that cause it. Difficulties experienced by students include conceptual errors, procedural errors as well as technical errors. Meanwhile, the lack of understanding the concept of root form resulting in misconception is a factor causing difficulties in the material.